The Double Dovish Effect: Reaksi Pasar Sektor Properti Dan Real Estate Terhadap Pemotongan Suku Bunga Serentak Oleh Bank Indonesia Dan The Federal Reserve - Ferdian, Rio Hendra; Azmiyanti, Rizdina (Fakultas Ekonomi Prodi Akuntansi, 2026)
Global monetary policy acts as a key driver of capital market dynamics, yet the impact of simultaneous domestic and international policy changes remains underexplored. This study examines market reactions to the “Double Dovish Effect,” characterized by simultaneous interest rate cuts by Bank Indonesia and the Federal Reserve, within the Indonesian property and real estate sector. A quantitative approach was employed using the event study method to analyze abnormal returns and cross-sectional analysis to identify the role of firm characteristics among 75 sampled companies. The findings indicate that market reactions are not immediately reflected in short-term stock price movements, suggesting that market participants had already anticipated the policy direction prior to the official announcement. Firm characteristics, specifically firm size, liquidity, and institutional ownership, play significant roles in shaping market responses compared to other financial indicators. This study concludes that market reactions to monetary policy are context-dependent and influenced by the long-term nature of the property sector. Future research is recommended to expand the scope to other sectors and include variables such as market sentiment. For investors, understanding sectoral business cycles is essential for managing risk, while regulators should prioritize transparency in policy communication to maintain market stability. Keywords: Event Study; Monetary Policy; Double Dovish Effect